Liderança autêntica: um estudo no varejo cearense - Tomaz, José Estevam (2020)
Modern society has become increasingly demand for demanding regarding the ethical stance of political, governmental and organizational leaders, raising the level of with an increased awareness of people and triggering leading to a the adoption of consumer behavior that considers the integrity an essential part of the increasingly in work and employment relationships, in addition to socio-environmental responsibility in the way of conceiving and conducting business. In this context, retail as is an activity that relates deals directly with to consumers and due to its relevant importance in the economic matrix, plays a crucial role in strengthening these relationships. Although leadership is an extremely explored theme subject in academic research, with several definitions, styles or models coexisting, authentic leadership is distinguished as one that is based on the dimensions of leading self-consciousness, on the internalized personal moral perspective, on the balanced information processing and on relational transparency. The objective purpose of this study is, therefore, to describe how authentic leadership is perceived by leaders and followers in retail in Ceará, based on using these four constitutive elements, based on the multidimensional model of Walumbwa et al (2008) and, for that. A quantitative research was carried out, carried out through an intersectional survey in a supermarket chain in Ceará. The data were obtained collected using the Authentic Leadership Questionnaire - ALQ scale and were the statistical analyses was performed using the SPSS. made treated using The Mann Whitney, Friedman and Kruskal-Wallis non-parametric tests were used for calculation of p-values and evaluation of the proposed associations calculated using the. The findings indicate that the authentic leadership practices, although present in the retail context, are not perceived in an equivalent way when comparing the averages of leaders and followers. The divergences are verified in the general perception of authentic leadership and in all dimensions of the model, except in the self-awareness dimension.